ANALISIS BIMBINGAN BELAJAR DI SD GMIT 27 MEBUNG - Gladys Itunde; Gabriel Malailak; Yessy Mata; Petrus Mau Tellu Dony; Jon Abraham Lalang Yame (JIP: Jurnal Ilmu Pendidikan, 2025)
This research aims to examine the role of tutoring in improving students' interest in learning at SD GMIT 27 Mebung, an elementary school that operates without a dedicated counseling teacher. The main issues raised are how this school implements counseling guidance services and the challenges faced in increasing students' interest in learning amidst limited resources and the influence of external factors. The research method used was descriptive qualitative with data collection techniques of in-depth interviews with class teachers as key informants. Data analysis was carried out thematically to identify strategies for collecting student interest and talent, handling social and disciplinary problems, collaboration with parents, and supervision and evaluation systems. The results showed that SD GMIT 27 Mebung implements integrated counseling guidance with the role of the class teacher as the main implementer. This system includes gradual data collection of students' interests and talents, individual and group social guidance services to overcome conflicts and bullying, as well as intensive handling of student attendance problems through home visits and provision of school supplies. Despite facing external challenges such as school conditions without parapets and the digital divide among students, this school has managed to make achievements in the development of students' interests and talents in the field of extracurricular activities.